A Large Sporadic Intra-abdominal Desmoid-Type Fibromatosis in a Young Male: A Case Report - Sioda, Natasha A.; Wakim, Andre A.; Wong, Tina; Patel, Shyamal; Coan, Kathryn; Row, David (Frontiers in Surgery, 2020)
Desmoid type fibromatosis (DTF) is a rare benign tumor of connective tissue origin. While these tumors are typically not malignant, they can exhibit aggressive growth patterns causing mass effect on surrounding organs. These tumors typically present in the extremities and abdominal wall, rarely occurring in the mesentery, and abdominal organs. Due to the rarity of this tumor and the variable size and origin, it is difficult to provide exact prognosis, recurrence, and treatment efficacy regarding desmoid tumors arising from the ileocolic mesentery. We present a case of a young male with a sporadic 31 × 25 × 12 cm DTF arising from the ileocolic mesentery that was complicated by mass effect on bowel and intra-abdominal organs requiring surgical intervention. On presentation, the patient exhibited weight gain and abdominal pressure. Abdominal distension without tenderness on palpation was noted on physical examination. The tumor biopsy confirmed the diagnosis of DTF. No evidence of familial adenomatous polyposis or Gardner syndrome was identified. The tumor was surgically excised and intimately associated with the bowel requiring ileocolonic resection with primary anastomosis. At 3-months follow up, surveillance MRI showed no residual or recurrent lesion. A multi-disciplinary approach to this patient's diagnosis and treatment allowed for an accurate diagnosis, efficient treatment, and follow up plan.